Effectiveness of front-of-pack nutrition labels on consumer behavior: implications for food labelling policy in Indonesia - Putri, Maulia Dewi Kurnia; Shaluhiyah, Zahroh; Indraswari, Ratih (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Non-communicable diseases (NCDs) such as obesity, diabetes, and hypertension have become significant global health challenges. One of the main factors contributing to this problem is the high consumption of packaged foods and beverages with excessive sugar, fat, and sodium content. Nutrition information labels have been identified as an effective strategy to raise awareness and encourage healthier consumption behavior change. Objective: This study aimed to evaluate the effectiveness of various nutrition information labeling systems, including Front-of-Pack Labeling (FOPL) such as Nutri-Score, Nutri-Grade, Health Star Rating, and warning-based labels, in improving consumer awareness, understanding, and consumption behavior. Methods: A scoping review was conducted using thirteen journals selected based on PRISMA guidelines, focusing on awareness, understanding, and changes in consumption behavior. Results: Intuitive visual labels increased consumer awareness by 75% and reduced sugar consumption by 1.51 grams per serving. Warning-based labels reduced purchases of unhealthy products by 17%. Conclusions: Effective nutrition labeling should adopt clear visual formats and be supported by public education. Further policy recommendations include integrating labeling with education campaigns and additional regulations, such as sugar taxes, to strengthen the long-term impact on healthier consumption patterns.